الدور الإعلامي المعرفي والقضية الفلسطينية - Adway, Abdallah Mahmoud (Penerbit Universiti Kebangsaan Malaysia, 2017)
Mass Media is an important source of knowledge received in the present era. It has a great power of effect and change the local, regional and global public opinion. It also the weapon has a role in the process of change in contemporary and conquest of baitul Maqdis. The study discusses the topic of bad image and the role of media massa in changing local and international opinion toward the Palestinian issue in preparation for freeing Baitul Maqdis. The study aims to discuss the role of media in the presentation of contemporary knowledge about Palestinian issue. The importance of the role in the creation of the world public opinion to achieve Israel according the Quranic. The study also revealed thaht, there are related to the Palestinian issue and the role of mass media about disadvantages of Israel in a language other than Arabic.